2020
DOI: 10.1111/dth.14425
|View full text |Cite
|
Sign up to set email alerts
|

Awareness on malignant melanoma and its prevention measures among Turkish cutaneous malignant melanoma patients: A tertiary cancer center experience

Abstract: Many genetic and phenotypic risk factors connected to malignant melanoma (MM) have been extensively studied and documented in the literature. Among them, sun exposure is considered one of the main causative factors for the development of MM. The risk is increased especially when vulnerable persons are subjected to sun intensely and intermittently. Therefore, creating a balance between sun exposure and protection measures, such as sun avoidance, is cru

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 6 publications
1
3
1
Order By: Relevance
“…The observed more frequent use of sunscreen with an SPF ≥ 30 among patients with a high education level is in agreement with previously published data ( 21 , 23 , 24 , 27 ). It could be due to a greater awareness of the possible consequences of melanoma ( 31 ) and also affects their children’s behavior ( 32 ).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The observed more frequent use of sunscreen with an SPF ≥ 30 among patients with a high education level is in agreement with previously published data ( 21 , 23 , 24 , 27 ). It could be due to a greater awareness of the possible consequences of melanoma ( 31 ) and also affects their children’s behavior ( 32 ).…”
Section: Discussionsupporting
confidence: 93%
“…Despite observing suboptimal sun protection behavior in both at-risk and melanoma patients ( 21 , 23 25 , 27 , 29 , 45 ),, we found that compared to the general population ( 17 ), our study participants had already better sun protective behaviors before study enrollment. Nevertheless, we demonstrated that verbal education about sun protection during standard skin cancer screening by a dermatologist further improved sunscreen application frequency and SPF.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…Almost the third part of patients (95, 33%) had information about skin cancer prevention and sun protection policy prior to diagnosis. As in the article of Tas et al, 3 higher education was found to be linked with higher awareness; also having another member of the family with a previous diagnosis of skin cancer was related to major awareness on sunscreening and measures to adopt. Moreover, patients with melanoma and actinic keratosis were observed to have better knowledge of sun exposure rules to follow.…”
mentioning
confidence: 69%
“…Several studies showed that ultraviolet radiation (UVR) is responsible for more than 65% of melanoma cases and 99% of basal cell and squamous cell carcinoma cases. 1,2 We read with great interest the article written by Tas et al 3 regarding the awareness on melanoma and the preventive measures to adopt in Turkish patients and we want also to share the experience recently conducted in our center, to assess the awareness on skin cancer and the adoption of preventive measures in Italian patients, extending it to melanoma and nonmelanoma skin cancer patients.…”
mentioning
confidence: 99%